2014
DOI: 10.1007/s10207-014-0268-3
|View full text |Cite
|
Sign up to set email alerts
|

Toward practical encrypted email that supports private, regular-expression searches

Abstract: In this paper, we develop a protocol to enable private regular-expression searches on encrypted data stored at a server. A novelty of the protocol lies in allowing a user to securely delegate an encrypted search query to a proxy, which interacts with the server where the user's data are stored encrypted to produce the search result for the user. The privacy of the query and the data are both provably protected against an arbitrarily malicious server and an honestbut-curious proxy under rigorous security defini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…However, this cryptosystem is also based on the same steps as its counterparts. Kocabas et al [58], Papadimitriou et al [59], Yakoubov et al [38], and Thayananthan and Albeshri [60] have explored security issues in big data and concluded that either homomorphic encryption based on ElGamal and Paillier algorithms suit most big data applications [61,62,35,10,63]. The other area that has received more attention regarding security and the prospect of using homomorphism is cloud computing, especially in respect to di erent healthcare application and data storage systems [51].…”
Section: Big Data and Cloud Computingmentioning
confidence: 99%
“…However, this cryptosystem is also based on the same steps as its counterparts. Kocabas et al [58], Papadimitriou et al [59], Yakoubov et al [38], and Thayananthan and Albeshri [60] have explored security issues in big data and concluded that either homomorphic encryption based on ElGamal and Paillier algorithms suit most big data applications [61,62,35,10,63]. The other area that has received more attention regarding security and the prospect of using homomorphism is cloud computing, especially in respect to di erent healthcare application and data storage systems [51].…”
Section: Big Data and Cloud Computingmentioning
confidence: 99%